The Effect of People and Processes on Customer Satisfaction at PT Sinar Rejeki Lembang - Yeni Rahmasari; Erna Pujihartanti (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study evaluates the empirical impact of people (X_1) and processes (X_2) on customer satisfaction (Y) within the retail automotive sector at PT Sinar Rejeki Lembang. Utilizing a quantitative design with Slovin’s sampling method (n = 100), primary survey data were analyzed through Ordinary Least Squares multiple linear regression alongside descriptive operational tracking. The econometric results indicate that both frontline personnel professionalism and procedural efficiency exert statistically significant positive effects on overall consumer evaluations, with personnel performance serving as the dominant driver. Operational tracking demonstrates sustained unit sales growth across early 2026, yet highlights notable friction points in administrative processing speed and complaint resolution. Descriptive indicator indices reveal that while frontline technical work quality achieved high consumer ratings, process issue responsiveness exhibited critical operational delays. This operational paradox underscores that rapid commercial expansion must be balanced with streamlined backend workflows and proactive frontline communication. To sustain consumer loyalty, automotive dealerships must integrate human resource development with administrative process digitization, ensuring consistent service execution across all post-encounter touchpoints.